2017
DOI: 10.1016/j.ebiom.2017.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Capacity of RASSF1A Promoter Methylation as a Biomarker in Tissue, Brushing, and Blood Samples of Nasopharyngeal Carcinoma

Abstract: Methylation of the RAS association domain family protein 1A (RASSF1A) promoter has been observed in nasopharyngeal carcinoma (NPC). This study investigated the correlation of RASSF1A promoter methylation with clinicopathological features and its utility as a diagnostic biomarker in NPC. A total of 926 patients with NPC and 495 non-tumor controls were analyzed in this study. RASSF1A promoter methylation was notably higher in NPC compared with non-tumor tissue, brushing and blood samples. RASSF1A promoter methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Screening for HNSCC depends on clinical symptoms and imaging examinations (laryngoscopy, computed tomography, magnetic resonance imaging, and positron emission tomography) and histopathological examination; however, owing to the non‐specificity of symptoms in early‐stage disease and ineffective conventional cancer‐related biomarkers, the early detection of HNSCC remains unsatisfactory. As they occur early in carcinogenesis and have other advantageous characteristics, abnormal methylation patterns represent potential markers for early detection of cancer and can even be non‐invasively detected in various body fluids (blood, bronchial aspirates, brushing, saliva, and urine) . In the present study, we constructed ROC curves and calculated the AUC to determine the diagnostic value of HOXA9 methylation for HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for HNSCC depends on clinical symptoms and imaging examinations (laryngoscopy, computed tomography, magnetic resonance imaging, and positron emission tomography) and histopathological examination; however, owing to the non‐specificity of symptoms in early‐stage disease and ineffective conventional cancer‐related biomarkers, the early detection of HNSCC remains unsatisfactory. As they occur early in carcinogenesis and have other advantageous characteristics, abnormal methylation patterns represent potential markers for early detection of cancer and can even be non‐invasively detected in various body fluids (blood, bronchial aspirates, brushing, saliva, and urine) . In the present study, we constructed ROC curves and calculated the AUC to determine the diagnostic value of HOXA9 methylation for HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the AUC was 0.95 and revealed efficient diagnostic power of CDKN2A promoter methylation in diagnosis of HNSCCs from precancerous samples, which can reveal that methylation is a relatively early molecular change during carcinogenesis as previous study concluded [13,104]. Some studies have suggested that DNA methylation can be detected in body fluid samples (blood, bronchial aspirates, brushing, saliva, and urine) as a noninvasive molecular biomarker for cancer screening and diagnosis [105][106][107]. We conducted a subgroup analysis based on sample type and the results showed that the AUC of saliva was 0.96, which was greater than that of tissue.…”
Section: Discussionmentioning
confidence: 76%
“…Some studies suggested DNA methylation as a promising tool for the diagnosis of cancer [88-91]. We analyzed the diagnostic effect of MLH1 promoter methylation in GC for the results with significant OR values and found that MLH1 promoter methylation could not distinguish GC from adjacent tissues, gastric adenomas, chronic gastritis, normal gastric mucosa, or normal healthy blood samples (i.e., the poor sensitivity value of < 0.5).…”
Section: Discussionmentioning
confidence: 99%